2021
DOI: 10.33578/jtlee.v4i2.7896
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Strengthening Character Educationin Gropol Batik in Soendari Batik Gallery

Abstract: Character education is an effort to create a generation that is intelligent and has noble character and has an Indonesian personality. The success of character education in learning does not necessarily come from the perspective of the cognitive domain, but rather how to balance cognitive, affective, and psychomotor domains whose estuary is to create a complete human being, likewise with cultural values. Foreign cultural values are growing rapidly along with technological advances, which have significantly shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…We need to know that batik was de jure recognized by UNESCO on October 2, 2009, so that it was designated as National Batik Day. Each region has its own uniqueness, there is one area that has distinctive batik, namely Tulungagung, which has penetrated the international scene (Muna Lia et al, 2016;Regina & Wijayaningputri, 2022;Tresnawati, 2018;Triwulandari, 2021) Batik is an example of this type of ethnoscience. This potential can be combined with the learning process because it has ethnochemical value (Bantul, 2021;Nazifah, 2022;Nurhayati et al, 2021).…”
Section: ▪ Introductionmentioning
confidence: 99%
“…We need to know that batik was de jure recognized by UNESCO on October 2, 2009, so that it was designated as National Batik Day. Each region has its own uniqueness, there is one area that has distinctive batik, namely Tulungagung, which has penetrated the international scene (Muna Lia et al, 2016;Regina & Wijayaningputri, 2022;Tresnawati, 2018;Triwulandari, 2021) Batik is an example of this type of ethnoscience. This potential can be combined with the learning process because it has ethnochemical value (Bantul, 2021;Nazifah, 2022;Nurhayati et al, 2021).…”
Section: ▪ Introductionmentioning
confidence: 99%
“…Compared to batik from other regions such as Solo and Jogja, Malangan batik is yet to be widely known, even though the aesthetic value of Malangan batik is no less interesting than batik from other regions in Indonesia [1]. The study of Elviera et al found that regional identity in various Malangan batik motifs greatly influences consumer purchasing decision [2].…”
Section: Introductionmentioning
confidence: 99%